Differences regarding job satisfaction and job involvement of psychologists with different dominant career anchors - CL Bester; T Mouton (AOSIS, 2006)
In order to contribute to higher levels of job satisfaction, job involvement , and productivity, a match or fit should be established between the dominant career anchor associated with a specific occupation and that of the employee. A career anchor is an individual's set of self-perceived talents, abilities, motives, needs and values that form the nucleus of one's occupational self-concept. Psychologists have always been part of the service orientated careers and therefore one would expect that it is likely that their dominant career anchor would be service orientation. If this is the case, psychologists with service as their dominant career anchor are supposed to have greater job satisfaction and job involvement compared to those with different career anchors. However, according to literature, this assumption is not necessarily correct. The primary goals of the current study were to determine whether in fact service is the dominant career anchor of psychologists in the Free State and whether there are significant differences regarding job satisfaction and job involvement between psychologists with and without service as their dominant career anchor. A third goal was to determine whether psychologists with different dominant career anchors differ significantly from one another regarding job satisfaction and job involvement. Questionnaires measuring career orientations, job satisfaction and job involvement were sent to 165 of the 171 registered psychologists in the Free State region. Only 75 psychologists (45,5%) responded which exceeded the traditional return rate of 20 to 30%. Due to the small sample of respondents, a nonparametric statistical test, namely the Mann Whitney U test was conducted to determine possible differences. An analysis of the data showed that 21 respondents had entrepreneurship as their dominant career orientation while 12 fell in the technical/functional, 12 in the challenging, 9 in the service and 8 in the autonomy categories of dominant career anchors. No significant differences regarding job satisfaction between psychologists with and without service as dominant career orientation could be determined. Both groups experienced a fairly high degree of job satisfaction and a higher level of intrinsic job satisfaction occurred compared to extrinsic job satisfaction. A significant difference between the two groups in terms of job involvement occurred. Psychologists with service as dominant career orientation showed a higher level of job involvement, although the degree of job involvement for both groups was fairly low. No significant differences regarding job satisfaction and job involvement among psychologists with different career orientations could be found.